All Days 2004
DOI: 10.4043/16589-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mad Dog Polyester Mooring - Prototype Testing And Stiffness Model for Use in Global Performance Analyses

Abstract: The Mad Dog Floating Production System (FPS) will be the first truss spar to use polyester for a permanent mooring system. The breaking strength of the polyester ropes is also the largest ever-made being in the 2000 mT range. As such, prototype testing to validate the breaking strength capacity of the spliced ropes was important along with gathering performance data of the ropes to be used in the mooring design and global performance analyses of the FPS. Since this is the first spar to use a polyester mooring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…An analysis method commonly used to design recent GoM FPSs (Petruska, 2004) uses the static drift stiffness to determine the new mean offset due to the mean load components of the environment. The dynamic stiffness is then used to determine the dynamic offsets due to the first and second order time varying components of the environment.…”
Section: Implementing Test Data Into Analysis Methodsmentioning
confidence: 99%
“…An analysis method commonly used to design recent GoM FPSs (Petruska, 2004) uses the static drift stiffness to determine the new mean offset due to the mean load components of the environment. The dynamic stiffness is then used to determine the dynamic offsets due to the first and second order time varying components of the environment.…”
Section: Implementing Test Data Into Analysis Methodsmentioning
confidence: 99%
“…[23] [24] [25] An insert was recently removed from the upper portion of a Mad Dog mooring leg for detailed examination and testing. Prototype samples of the polyester rope were extensively tested to determine static and dynamic stiffness characteristics.…”
Section: Mad Dogmentioning
confidence: 99%
“…Results from the TTI Durability JIP [10] and other testing [11] have shown that axial compression fatigue is not a design issue for these synthetic fibers and can be treated the same as axial tension fatigue. Results from the TTI Durability JIP [10] and other testing [11] have shown that axial compression fatigue is not a design issue for these synthetic fibers and can be treated the same as axial tension fatigue.…”
Section: Overview Of Api Rp 2sm Addendummentioning
confidence: 99%
“…Rope Stiffness and Elongation -Since 2SM was written, the concept of a polyester rope static stiffness has been realized and better understood [11]. Static stiffness is the stiffness the rope exhibits under steady loads and thus the mooring designer must understand the rope elongation behavior when the rate of loading is much slower than typical wave or low frequency motions, for example for a spar during a loop current event.…”
Section: Overview Of Api Rp 2sm Addendummentioning
confidence: 99%